Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s11418-009-0381-1
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis of an antiviral fraction of Radix astragali using HPLC–DAD–ESI–MS/MS

Abstract: Radix astragali (Huangqi in Chinese) is a well-known traditional Chinese medicinal herb that has been used clinically in China for centuries to cure various diseases. To profile the antiviral constituents of this herb, a high-performance liquid chromatography-diode array detector-electrospray ionization-tandem mass spectrometry (HPLC-DAD-ESI-MS/MS) analytical method was developed to separate and determinate the active part of the extract of Radix astragali, which showed potent inhibition of several viruses. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Radix Astragali is also commonly used as immunomodulating agent to stimulate the immune system of immunodeficient patients. Moreover, it has been reported that herbal formulations containing Radix Astragali and some of its constituents could produce hepatoprotective [24], antiviral [25] and antioxidative effects [26]. Recently, evidence from various animal and clinical studies has demonstrated that Radix Astragali may possess anticarcinogenic property [27], which could attenuate the systemic side effects of conventional antineoplatic drugs [28].…”
Section: Discussionmentioning
confidence: 99%
“…Radix Astragali is also commonly used as immunomodulating agent to stimulate the immune system of immunodeficient patients. Moreover, it has been reported that herbal formulations containing Radix Astragali and some of its constituents could produce hepatoprotective [24], antiviral [25] and antioxidative effects [26]. Recently, evidence from various animal and clinical studies has demonstrated that Radix Astragali may possess anticarcinogenic property [27], which could attenuate the systemic side effects of conventional antineoplatic drugs [28].…”
Section: Discussionmentioning
confidence: 99%
“…A. mongholicus has been broadly utilized as a principal herbal medicine in China, including Northeast, North, and Northwest China, as well as in Mongolia and Korea [ 3 ]. Based on pharmacological studies and clinical practice, the dried roots of A. mongholicus have good potential therapeutic applications, including vital-energy tonification, abscess drainage, diuretic properties, skin reinforcement, and tissue regeneration [ 4 6 ]. Recent studies revealed that these bioactivities are mainly associated with isoflavonoids and triterpenoid saponins [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, AR is mainly used in the treatment of nephritis, diabetes and cancer, and the saponins, flavonoids and polysaccharides contained in the herb are considered as the main components contributing to its clinical therapeutic effect [1,9]. Thus, these compounds have been tentatively assigned as the chemical markers for the quality control of AR, and a variety of analytical methods have been developed for characterizing the flavonoids and saponins of AR [[10], [11], [12], [13], [14], [15], [16]]. Among them, high performance liquid chromatography (HPLC) is more frequently used.…”
Section: Introductionmentioning
confidence: 99%